THE VIOLATING OF POLITENESS MAXIMS FOUND IN CLASSROOM INTERACTION BETWEEN TEACHER AND ENGLISH STUDENTS - Devie Reztia Anjarani (The Ellite of Unira, 2022)
Politeness is a way to convey expressions smoothly, nicely and politely in verbal communication. Politeness is also required to be carried out in official forums such as the learning and teaching process in the classroom. In this case, the researcher is interested and raises the title of violation from the maxim of politeness in language teaching and learning interactions in the seventh semester students. The purpose of this study is to describe objectively the politeness maxims violated by teacher or students in the class interaction. This research is a qualitative research and the source of data in this study is in the form of conversations between students and teachers that have been copied or converted into written form. Based on the data analysis, it can be concluded that the deviation of politeness maxims in teaching and learning interactions occurs in all politeness maxims, namely the maxim of wisdom, maxim of generosity, maxim of praise, maxim of humility, maxim of agreement, and maxim of sympathy. The maxim that most violated appear in wisdom maxim, generosity maxim, agreement maxim, and sympathy maxim with three violation of each. While the violation that occurs the least is the maxim of humility which only appears once. Violations from these maxims occur due to various behaviors, such as giving harm to others, having bad thoughts, criticizing and putting others down, self-